PENGARUH STRUKTUR AKTIVA, PERTUMBUHAN, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PERUSAHAAN - Anita Dwi Lestari (Jurnal Riset Akuntansi dan Keuangan, 2010)
Capital structure is one of the important information for companies to archieve their goals. The aim of this research is to analyze the effect of asset structure, growth, and liquidity toward capital structure. The sample of this research are 96 observations from listed public manufacturing companies ofindonesian stock exchange year 2007-2009. Sample collected using Cluster Proporsional Random Sampling. Hypothesis tested using multiple regression and the result shows only liquidity has significance effect toward capital structure. Whereas asset structure and growth do not have significance effect toward capital structure Keywords:Capital Structure, Asset Structure, Growth, Liquidity